PENGEMBANGAN MODEL APE BONEKA JARI SARONDE UNTUK MENINGKATKAN KEMAMPUAN BAHASA DI TAMAN KANAK-KANAK DI KECAMATAN KWANDANG - Lina A. Husain; Abdul Hamid Isa; Muhamad Zubaedi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to develop a model of Educational Play Tools (APE) in the form of Saronde Finger Dolls based on local culture to improve early childhood language skills in Kindergarten of Kwandang District, North Gorontalo Regency. The method used is research and development with a mix-method approach, which combines qualitative and quantitative data. Model development is carried out through several stages, ranging from identification of potentials and problems, product design, expert validation, design revision, to trials limited to 30 kindergarten children. The validation results from material and media experts show that the developed APE is included in the category of very valid. The limited trial showed a significant improvement in children's language skills, with an average pre-test score of 62.3 and a post-test of 83.5. The results of the paired sample t-test analysis showed a calculated t value of 20.27, greater than the t table of 2.045 (α = 0.05), which means that there was a significant difference before and after the use of the model. These findings are supported by observational and interview data that show an increase in children's interest, participation, and courage in communicating. This model is considered effective, contextual, and has the potential to strengthen the preservation of local culture in learning